Organometallic sulfur complexes: reactivity of the hydrogen sulfide anion with cobaloximes. (26th March 2015) - Strianese, Maria; Mirra, Silvia; Bertolasi, Valerio; Milione, Stefano; Pellecchia, Claudio
Abstract : The hydrogen sulfide anion selectively and reversibly displaces pyridine in cobaloxime. A rare trisulfido-bridged dinuclear complex was isolated and characterized. Abstract : The reaction of alkylcobaloxime [Co(dmgH)2 (CH2 CH3 )(py)] (1 ) (dmgH = the anion of dimethyl-glyoxime) with KSH in water solution resulted in the selective displacement of the pyridine axial ligand affording the derivative K[Co(dmgH)2 (CH2 CH3 )(SH)] (2 ). An 1 H– 1 H EXSY experiment revealed that the substitution is reversible and occurs in a slow exchange regime. Attempts to grow crystals of the HS − adduct led to isolation of a rare example of the unexpected trisulfido-bridged dinuclear complex K2 [Co2 (dmgH)2 (CH2 CH3 )2 (μ-S3 )]. It was shown that the glyoximato ligands provided the metal centre with a coordination environment quite robust to prevent decomposition and constitute a suitable platform for developing the chemistry of organometallic complexes bearing hydrogensulfido or oligosulfido ligands.